(untitled) (Jurnal Manajemen Perhotelan, 2007)
Surabaya Plaza Hotel (SPH) is very well accepted by its present clientele, but nonetheless the guests have a few factors of complaint. The overall image of SPH is highly positive. SPH also provides superior quality and services. Providing the guests with satisfactory services and experiences is a key to success in the hotel industry. In order to reach a supreme level of customer satisfaction, the guests’ opinions and ideas should be employed on ongoing processes of total quality management.